2020
DOI: 10.1111/xen.12664
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone receptor knockout to reduce the size of donor pigs for preclinical xenotransplantation studies

Abstract: Background Many genetically multi‐modified donor lines for xenotransplantation have a background of domestic pigs with rapid body and organ growth. The intrinsic growth potential of porcine xeno‐organs may impair their long‐term function after orthotopic transplantation in non‐human primate models. Since growth hormone is a major stimulator of postnatal growth, we deleted its receptor (GHR‐KO) to reduce the size of donor pigs in one step. Methods Heart weight and proteome profile of myocardium were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…Recently, Hinrichs et al have produced GHRKO pigs in order to address intrinsic organ growth. They demonstrate that GHRKO pigs have slow or reduced growth, including their organs’ growth, compared to normal wild-type pigs ( 61 , 104 107 ). Recently, Goerlich, et al have examined intrinsic and extrinsic causes of graft growth after transplantation in an OHTx model using “multi-gene” pigs growth hormone receptor knockout pigs (GHRKO) ( 69 ).…”
Section: Overcoming the Challenges For Successful Cardiac Xenotranspl...mentioning
confidence: 99%
“…Recently, Hinrichs et al have produced GHRKO pigs in order to address intrinsic organ growth. They demonstrate that GHRKO pigs have slow or reduced growth, including their organs’ growth, compared to normal wild-type pigs ( 61 , 104 107 ). Recently, Goerlich, et al have examined intrinsic and extrinsic causes of graft growth after transplantation in an OHTx model using “multi-gene” pigs growth hormone receptor knockout pigs (GHRKO) ( 69 ).…”
Section: Overcoming the Challenges For Successful Cardiac Xenotranspl...mentioning
confidence: 99%
“…Genetically modified swine with antigenic knockouts and human transgene knock‐ins are used as xenograft donors, along with CD40/CD40L co‐stimulation blockade, in order to produce xenografts that are immunocompatible for human transplantation 7 . GHRKO in pigs as an additional knockout has been proposed to address intrinsic factors of graft growth; namely, the exponential growth seen in age‐matched xenograft donors 8 . Similar to mouse models, GHRKO pigs are characterized by decreased circulating IGF‐1, proportional growth retardation, and mirror the human disease Laron syndrome, with a similar phenotype 9 …”
Section: Figurementioning
confidence: 99%
“…7 GHRKO in pigs as an additional knockout has been proposed to address intrinsic factors of graft growth; namely, the exponential growth seen in age-matched xenograft donors. 8 Similar to mouse models, GHRKO pigs are characterized by decreased circulating IGF-1, proportional growth retardation, and mirror the human disease Laron syndrome, with a similar phenotype. 9 We demonstrated that the addition of GHRKO to these genetically engineered cardiac xenografts, in order to reduce xenograft growth, prolongs survival up to 9 months (264 days).…”
mentioning
confidence: 99%
“…Xeno-organs donated by genetically modified pigs carrying the genetic background of domestic pigs can grow rapidly; this can generate incompatibility with recipients and impair their long-term function after transplantation. Growth hormone receptor ( GHR )-deficient pigs with reduced organ size [ 73 , 74 ] and subsequent GHR / GGTA1 double-knockout pigs expressing the human cluster of differentiation ( hCD46 ) and human thrombomodulin ( hTHBD ) [ 75 ] have been generated by gene editing. This approach will improve the implementation of xenotransplantation.…”
Section: Recent Trends In Gene Editing In Pigsmentioning
confidence: 99%